Contrasting effects of rising CO2 on primary production and ecological stoichiometry at different nutrient levels. (12th May 2014) - Verspagen, Jolanda M. H.; Van de Waal, Dedmer B.; Finke, Jan F.; Visser, Petra M.; Huisman, Jef; Grover, James
Abstract Although rising CO2 concentrations are thought to promote the growth and alter the carbon : nutrient stoichiometry of primary producers, several studies have reported conflicting results. To reconcile these contrasting results, we tested the following hypotheses: rising CO2 levels (1) will increase phytoplankton biomass more at high nutrient loads than at low nutrient loads, but (2) will increase their carbon : nutrient stoichiometry more at low than at high nutrient loads. We formulated a mathematical model to predict dynamic changes in phytoplankton population density, elemental stoichiometry and inorganic carbon chemistry in response to rising CO2. The model was tested in chemostat experiments with the freshwater cyanobacterium Microcystis aeruginosa. The model predictions and experimental results confirmed the hypotheses. Our findings provide a novel theoretical framework to understand and predict effects of rising CO2 concentrations on primary producers and their nutritional quality as food for herbivores under different nutrient conditions.